2016
DOI: 10.21577/0103-5053.20160228
|View full text |Cite
|
Sign up to set email alerts
|

Conyza canadensis: Green Extraction Method of Bioactive Compounds and Evaluation of Their Antifungal Activity

Abstract: Synthetic fungicides are a common treatment for post-harvest diseases in fruits, although demand is increasing for alternatives such as biopesticides. The aim of this work was to investigate the presence of naturally occurring antifungal compounds in Brazilian specimens of the weed Conyza canadensis. Two compounds [(4Z)-lachnophyllum lactone and (4Z,8Z)-matricaria lactone] were isolated and their antifungal activities were evaluated against eight postharvest disease fungi. Aspergillus niger, Cladosporium sp., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The isolated substance, (4Z)-lachnophyllum lactone (LACH), was characterized as described by Porto et al (2017). To confirm the structure of this compound, 1 H and 13 C nuclear magnetic resonance F I G U R E 1 Bioactive substance isolated from Conyza canadensis (4Z)-lachnophyllum lactone (LACH) (NMR) spectra were obtained using either a Bruker AVANCE 400 MHz spectrometer or a Bruker AVANCE 500 MHz spectrometer and CDCl 3 as solvent.…”
Section: Isolation and Identification Of Lach From C Canadensismentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated substance, (4Z)-lachnophyllum lactone (LACH), was characterized as described by Porto et al (2017). To confirm the structure of this compound, 1 H and 13 C nuclear magnetic resonance F I G U R E 1 Bioactive substance isolated from Conyza canadensis (4Z)-lachnophyllum lactone (LACH) (NMR) spectra were obtained using either a Bruker AVANCE 400 MHz spectrometer or a Bruker AVANCE 500 MHz spectrometer and CDCl 3 as solvent.…”
Section: Isolation and Identification Of Lach From C Canadensismentioning
confidence: 99%
“…Queiroz et al (2012) performed the systematic fractionation guided by bioassays using extract of C. canadensis and identified three substances with antifungal activity among them (4Z)-lachnophyllum lactone (LACH) (Figure 1). According to Porto et al (2017), this substance showed significant in vitro activity against P. digitatum.…”
mentioning
confidence: 99%
“…The dispersions were filtered and analyzed by GC-MS (Aligent 5975C TAD Series GC/MSD System,©Aligent Technologies, Inc., CA, USA) using the following chromatographic conditions: (i) Sample: injected volume of 2.0 μl; (ii) Column: HP-5MS, 5% diphenyl, 95% dimethylpolysiloxane (30 m × 0.25 mm × 0.25 μm); (iii) Drag gas: He (99.9999) → 1 ml/min; (iv) Injector: 280°C, Split 1:10 (leaf and root) and 1:1 (stem); (v) Oven: 50°C (2 min) → 250°C (5°C/1 min); 250°C (10 min); and (vi) Detector: Linear quadrupole mass spectrometer, Ionization source (impact by electrons → 70 eV), Scan mode (0.5 s/scan), Mass range ], Line transfer (280°C) and Filament (off at 7.0 min). The Mass Spectral Database (NIST 11) was used to identify compounds detected in the chromatograms [28].…”
Section: Qualitative Analysis By Gas Chromatographymass Spectrometry mentioning
confidence: 99%
“…Horseweed leaves used for toothache leaves [21] decoction of herb used to treat diarrhea herb [23] Mikasuki and Seminole Native Americans used the plant to treat sore throats and respiratory complaints [146] Whole plant: β-sitosterol, stigmasterol, β-sitosterol 3-O-β-D-glucoside, harmine, and sphingolipid [147] Aerial parts: triterpenoid erigeronol (showed potent anti-melanoma cytotoxicity) [149] Whole plant: conyzolide, conyzoflavone (both showed antimicrobial activities) [150] Whole plant: 8R,9R-dihydroxymatricarine methyl ester, matricarine methyl ester, matricarine lactone, Aerial parts: enyne derivatives, (2Z,8Z)-matricaria acid methyl ester, (4Z,8Z)-matricaria lactone, and (4Z)-lachnophyllum lactone [153] Aerial parts: (4Z)-lachnophyllum lactone, (4Z,8Z)-matricaria lactone, (2Z,8Z)-matricaria acid methyl ester; (4Z)-lachnophyllum lactone and (4Z,8Z)-matricaria lactone showed antifungal activity against Aspergillus niger, Cladosporium sp., and Penicillium digitatum [154] Flowering parts: polyphenolic-polysaccharide (anticoagulant, antiplatelet activity) [155] Roots: dihydropyranones conyzapyranone A and B; 4Z,8Z-matricaria-γ-lactone, 4E,8Z-matricaria-γ-lactone, 9,12,13-trihydroxy-10(E)-octadecenoic acid, epifriedelanol, friedelin, taraxerol, simiarenol, spinasterol, stigmasterol, β-sitosterol, and apigenin; conyzapyranone B, 4E,8Z-matricaria-γ-lactone, and spinasterol showed cytotoxic activity [156,157] Roots: triterpenoid 3β-erythrodiol (inhibits MKN-45 gastric cell proliferation) [158] Roots: salicylic acid, methyl gallate [159] Roots: lanostane triterpenoids conyzagenin-A, conyzagenin-B [160] Coreopsis tinctoria Nutt. Asteraceae Tickseed root tea for diarrhea root [15] Plant: polyacetylenes, (2S)-(3Z,11E)-decadiene-5,7,9-triyne-1,2-diol and (2R)-(3E,11Z)-decadiene-5,7,9-triyne-1,2-diol [170] Plant: seven compounds made up the major contributions of antioxidant activity in C. tinctoria, including okanin, isookanin, marein, flavanomarein, 5,7,3 ,5 -tetrahydroxyflavanone-7-O-glucoside, 3,5-dicaffeoylquinic acid, and chlorogenic acid [171] Flowers: C 14 polyacetylene glycosides coreosides A-D [172] Buds: C 14 polyacetylene glycosides coreosides E and F [173] Flowers: C 14 polyacetylene glycosides coreosides A, B, D, and E [174] Flowers: chalcone marein, flavanone flavanomarein [175] Flowers Fruits: flavonoids (marein, flavanomarein, quercetagetin-7-O-glucoside, okanin aurone, leptosidin, luteolin, apigenin) and phenolic acids (chlorogenic acid, caffeic acid)…”
Section: Asteraceaementioning
confidence: 99%